Charnockite Massifs: Key to Tectonic Evolution of the Eastern Ghats Belt, India, and Its Columbia Connection - Bhattacharya, Samarendra; Basei, M.; Kar, R. (Canadian Research & Development Center of Sciences and Cultures, 2014)
The Eastern Ghats Granulite Belt, India, with two major lithological associations: charnockites and meta sedimentary granulites, is characterized by polyphase deformation and complex, possibly multiple granulite events. Barring the cratonic margins in the north and west, two distinct crustal domains have been identified: the Eastern Ghats Province (EGP) and Ongole domain, separated by the Godavari graben. These domains also have distinct geochronological record of granulite event: in the EGP the first granulite event has been recorded as between 1.2 and 0.9 Ga; while in the Ongole domain the granulite event is recorded as 1.6 - 1.7 Ga. However, charnockite-massifs in both the domains, interpreted as product of deep crustal anatexis under granulite facies conditions, could provide a link in tectonic evolution of the EGB as a whole. LA-ICP-MS analysis of zircon spot ages of two charnockite massifs reveals vestiges of the1.6 Ga charnockite magmatism in the EGP as identical to that in the Ongole domain. Another charnockite massif in the EGP records concordant zircon spot age of 940 Ma, but single spot age of 990 Ma could indicate a prolonged UHT event. Thus magmatic charnockites of intracrustal melting origin could represent two granulite events, at ca. 1.6 and 1.0 Ga in the Eastern Ghats Belt. Also, accretionary orogenic processes of the Supercontinent Columbia might have encompassed the Eastern Ghats Belt with Australia, Antarctica and Laurentia.